Becoming a missionary church : Lesslie Newbigin and contemporary church movements - Goheen, Michael W., 1955-; Sheridan, Timothy M., 1973- (Grand Rapids, MI. Baker Academic, 2022)
"Offers a historical assessment and balanced critique of contemporary church movements, especially in light of missional ecclesiology"--
Includes bibliographical references and index.
Keywords: Newbigin, Lesslie; Missions -- Theory; Church